Depression symptoms and associated factors in healthcare university students (Research, Society and Development, 2022)
Depressive disorders are among the main psychiatric diseases that affect the population, including university students. In this context, this study sought to assess the prevalence of depression symptoms and associated factors in university students in the health area. This is an analytical, cross-sectional study with a quantitative approach. Data collection took place through the application of a questionnaire that addressed sociodemographic and behavioral aspects, health status and assessment of the anthropometric profile. 364 university students participated and the prevalence of symptoms of depression was 19.2%. Skin color (p = 0.048), body image dissatisfaction (p = 0.032), physical activity level (p = 0.029), self-rated health (p = 0.001) and anxiety symptoms (p = 0.001) were associated with depression symptoms. It is concluded that depressive symptoms are prevalent among university students and that sociodemographic, behavioral and health status are associated with these symptoms.